Detecting and preventing unauthorised computer access on a physical network system - Mohd. Shariff, Muhammad Reza (2008)
Threats are nuisance to the information technology world. Today we have different kind of threats which includes, hacking, viruses and sniffing. However most threats in information technology systems come within, whereby threats come within the internal network. These internal threats may come from disgruntle staffs, hackers, virus attack, or even corporate espionage. At any corporate network, a number of active port are located through out the organization, this could be a loophole for a security breach. A hacker may enter the network by inserting a cable to an active port which is not secure within the building. Sometimes system administrator does not have the time to check on every connection that are active and not in use on a daily basis. This may lead to an intrusion that will compromise the network system. On the other hand if several virus outbreaks happen at a corporate network system the network system maybe halted or collapse thus paralyzing the whole network infrastructure. A solution to block any computers that had been infested by virus is needed. The purpose of this research is to build an application that eliminate and prevent any illegal workstation from entering the network. These illegal workstation includes workstation that has no rights to enter the network, workstation that are not owned by the company or staffs, and workstation that has been infected by virus or have malicious intention to the corporate network. The system shall stop any workstation by determining the IP address or MAC address or both that is unknown to the system administrator or had been infected by viruses from the network. This is to ensure that these workstations shall not be able to attack the network system or spreading viruses throughout the network. With the system, system administrators do not need to check on every workstation on the corporate network for threats thus minimize manpower.